EVALUATION OF SUSTAINABLE AQUACULTURE PRACTICES IN UJUNGPANGKAH-GRESIK PONDS-GRESIK - Nuhman Nuhman; Robert Tambun; Supartono Supartono (Universitas Mataram, 2026)
This study aims to evaluate the sustainability level of aquaculture practices in the pond area of Ujungpangkah-Gresik District, Gresik, and to formulate development strategies. Data were collected through field observation, interviews, water quality measurements, and documentary studies. Descriptive analysis was used to assess the sustainability level based on ecological, economic, social, and technological dimensions, while SWOT analysis was used to formulate strategies. The results show that aquaculture practices in Ujungpangkah-Gresik are in the moderately sustainable category. The economic and social aspects are relatively good, while the ecological aspect remains the main challenge, characterized by fluctuating water quality and suboptimal waste management. SWOT analysis identified strengths such as farmers' experience and extensive land potential, as well as opportunities from technological developments. Recommended development strategies include improved environmental management, modernization of cultivation technology, strengthening of farmer institutions, and business diversification. This study concludes that the key to sustainability lies in strengthening ecological aspects, increasing farmer capacity, and adopting environmentally friendly technologies. Key words: Sustainable Aquaculture, Evaluation, Water Quality, SWOT, Ujungpangkah-Gresik-Gresik